Early kidney injury in immunoglobulin A vasculitis: Role of renal biomarkers. Issue 10 (19th August 2021) - Türe, Esra; Yazar, Abdullah; Akın, Fatih; Topcu, Cemile; Aydın, Arif; Balasar, Mehmet; Ataş, Bülent
Abstract: Background: We aimed to determine whether urine kidney injury molecule 1 (KIM‐1) and neutrophil gelatinase‐associated lipocalin (NGAL) can be used as early noninvasive biomarkers of kidney injury in immunoglobulin A vasculitis. Methods: Patients who were diagnosed with immunoglobulin A vasculitis were included in the study. Urine samples were collected for determination of urine KIM‐1 and NGAL levels. The control group consisted of age‐matched healthy children. Results: Sixty‐one patients who were diagnosed with immunoglobulin A vasculitis were included in the study; 37.7% of these patients were determined to have renal involvement. Median KIM‐1 was found to be significantly higher in the patient group (69.59 pg/mL) than the control group (40.84 pg/mL) ( P = 0.001). Median NGAL was determined to be statistically significantly higher in the patient group (59.87 ng/mL) compared with the control group (44.87 ng/mL) ( P = 0.013). In 23.6% of the patients without renal involvement at admission renal involvement developed within the following 6 months. When median KIM‐1 and NGAL at admission of these patients were compared with the control group, they were determined to be statistically significantly higher ( P = 0.001, P = 0.003). Conclusions: The fact that our patients with late‐term nephropathy had no hematuria and / or proteinuria and that KIM‐1 and NGAL levels were determined to be high indicates that these biomarkers might be potentially reliable, noninvasive and early determinants of kidney injury.